2013
DOI: 10.1186/2050-7771-1-9
|View full text |Cite
|
Sign up to set email alerts
|

New urinary biomarkers for diabetic kidney disease

Abstract: Diabetic kidney disease is the leading cause of end-stage renal disease in developed and developing countries. Microalbuminuria is the gold standard for detection and prediction of diabetic kidney disease and cardiovascular risk disease in clinical practice. However, microalbuminuria has several limitations, such as lower sensitive, larger variability. It is urgent to explore higher sensitivity and specificity for earlier detection of diabetic kidney disease and more accurate prediction of the progression to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 30 publications
0
30
0
1
Order By: Relevance
“…CP is a major hypoxia-activated systemic NO oxidase that seems to be able to function in both antioxidant and pro-oxidant capacities ( Fox et al, 1995). It was reported that CP may be a potential diagnostic biomarker for diabetic nephropathy (Ito et al, 2008) and new potential urinary biomarker (Wang et al, 2013). In this study, CP levels of the renal tissues were increased significantly in Mtx administrated group compared to control.…”
Section: Discussionmentioning
confidence: 45%
“…CP is a major hypoxia-activated systemic NO oxidase that seems to be able to function in both antioxidant and pro-oxidant capacities ( Fox et al, 1995). It was reported that CP may be a potential diagnostic biomarker for diabetic nephropathy (Ito et al, 2008) and new potential urinary biomarker (Wang et al, 2013). In this study, CP levels of the renal tissues were increased significantly in Mtx administrated group compared to control.…”
Section: Discussionmentioning
confidence: 45%
“…73 For urinary ceruloplasmin, this coppertransporting serum protein is filtered with difficulty through the glomerular barrier because it is negatively charged like IgG. 74 Similar to urinary transferrin and urinary IgG, urinary ceruloplasmin can predict DN earlier than albuminuria in T2DM patients; in fact, the values of the three markers can be elevated concomitantly. 75 Both laminin and type IV collagen are components of glomerular basement membrane, although the latter is also a component of mesangial matrix.…”
mentioning
confidence: 99%
“…A recent study showed that urinary MCP-1 was significantly higher in patients with doubling of serum creatinine or death, in the Cox regression, urinary MCP-1 excretion was positively associated with the risk of serum creatinine doubling or death, and urinary MCP-1 remained as significant independent predictor of this primary outcome (doubling of serum creatinine or death) (Titan et al 2012). All the data mentioned above indicated that urinary MCP-1 could be a prognostic biomarker for progression of DN, further investigations need to be performed to confirm whether urinary MCP-1 has a role in the setting of normoalbuminuria and microalbuminuria in DN (Wang et al 2013). …”
Section: 2monocyte Chemoattractant Protein-1 (Mcp-1)mentioning
confidence: 99%
“…It is widely accepted that glomerular podocyte number declines plus urinary excretion of podocytes play an important role in the progression of DN (Weil et al 2011). Urinary podocytes can be detected in diabetic patients with microalbuminuria and overt albuminuria (Nakamura et al 2000), monitoring urinary podocytes can reveal potential urinary markers for early diagnosis of DN(Dalla Vestra et al 2003, Wang et al 2013.Studies showed that podocyte specific protein synaptopodin, podocin and nephrin were downregulated in DN renal biopsies, urinary nephrin levels (nephrinuria) were found to be present in the microalbuminuric, macroalbuminuric patients and normoalbuminuric patients at different ratios, suggesting that nephrinuria might be an early biomarker of DN (Patari et al 2003). Urinary podocalyxin were found to be elevated in 53.8% patients at normoalbuminuric stage, 64.7% at the microalbuminuric stage and 66.7% at overt proteinuric stage, which suggested that urinary podocalyxin could be a biomarker for detecting early podocyte injury of DN (Hara et al 2012).…”
Section: Podocytes and Podocyte-associated Moleculesmentioning
confidence: 99%